The Impact of Helminth Infection on the Incidence of Metabolic Syndrome: A Systematic Review and Meta-Analysis - Rennie, Claire; Fernandez, Ritin; Donnelly, Sheila; McGrath, Kristine CY (Frontiers in Endocrinology, 2021)
Background: There are a growing number of publications that report an absence of inflammatory based disease among populations that are endemic to parasitic worms (helminths) demonstrating the ability of these parasites to potentially regulate human immune responses. The aim of this systematic review and meta-analysis was to determine the impact of helminth infection on metabolic outcomes in human populations. Methods: Using PRISMA guidelines, six databases were searched for studies published up to August 2020. Random effects meta-analysis was performed to estimate pooled proportions with 95% confidence intervals using the Review Manager Software version 5.4.1. Results: Fourteen studies were included in the review. Fasting blood glucose was significantly lower in persons with infection (MD -0.22, 95% CI -0.40- -0.04, P=0.02), HbA1c levels were lower, although not significantly, and prevalence of the metabolic syndrome (P=0.001) and type 2 diabetes was lower (OR 1.03, 95% CI 0.34-3.09, P<0.0001). Infection was negatively associated with type 2 diabetes when comparing person with diabetes to the group without diabetes (OR 0.44, 95% CI 0.29-0.67, P=0.0001). Conclusions: While infection with helminths was generally associated with improved metabolic function, there were notable differences in efficacy between parasite species. Based on the data assessed, live infection with S. mansoni resulted in the most significant positive changes to metabolic outcomes.